HbA1C in Patients with Gestational Diabetes Mellitus - Ahmed, Farhena; Hoque, Mahmudul; Alam, ASM Towhidul; Ahmed, Shaheda; Tasnim, Nayeema (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2013)
Introduction: Approximately 7% of all pregnancies are complicated by Gestational Diabetes Mellitus.. The study was designed to determine the relationship between HbA1c & Gestational Diabetes Mellitus to reduce complications & monitoring treatment. Methods: The present cross-sectional comparative study was carried out in departments of Biochemistry and Obstetrics & Gynecology, Chittagong Medical College, Chittagong, Bangladesh. The data were collected by a structured questionnaire including age, socioeconomic condition, gravida, para, blood pressure, BMI, FBS, PPBS & Family H/O diabetes mellitus. Patients suffering from shortened red blood cell life span, sickle cell disease or any other condition that could result in premature red blood cell death and longer red blood cell life span, such as vitamin B12 or folate deficiency were excluded. Total 110 pregnant women were included in this study. Among them 70 were considered as case (whose FBS &PPBS according to ADA criteria of FPG value of ?5.3mmol/l and the WHO criteria of a 2-h PPPG value of ?7.8mmol/l) and 40 were considered as control (whose FBS <5.3mmol/L & PPBS <7.8mmol/L). HbA1c were measured in all sample. Results: Study showed that HbA1c( 6%) were more increased in GDM patients than that of the normal pregnancy( (6.95±1.38% Vs 5.05 ±0.27 %, p<0.001).Result showed that percentage of raised plasma HbA1c is more in GDM patients than that of the normal pregnancy (57.1%,P=<0.001).Pearson,s correlation coefficient (r) showed that there are positive correlation between Blood Glucose Level & HbA1c (Fasting Blood Glucose & HbA1c,r=0.869,p=<0.001 and Post Prandial Blood Sugar & HbA1c, r=0.507, p=<.0.001). Conclusion: Significantly raised level HbA1c in GDM help to formulate a management plan and thereby reduce the complications of this disease. Chattagram Maa-O-Shishu Hospital Medical College Journal Volume 12, Issue 3, September 2013: 11-15